2000
DOI: 10.1002/(sici)1521-379x(200004)52:2/3<63::aid-star63>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Functional Properties of Banana Flour from Different Varieties

Abstract: The chemical composition and some physico‐chemical characteristics of the flour obtained from eight different banana varieties are presented. The flour was prepared by freeze‐drying a homogenate of green banana pulp. Amylose, starch, dietary fiber, protein, ash, moisture and lipid contents were determined. Viscosity and gelatinization of starch were also investigated. Banana flour is rich in starch granules. Peak temperature of gelatinization varied from 68 to 76 °C according to the variety. All of them showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
104
4
12

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 14 publications
22
104
4
12
Order By: Relevance
“…An important parameter of an ingredient used in bakery formulations is its lipid content. The BF analysed in this work had a lipid content of 2.69%, higher than the values reported by others for BF prepared from diverse unripe banana, being estimated to be between 0.33 and 0.82% [17]. The high lipid content reported here (in this work) could be due to that in our study a complete banana was used (peel and pulp).…”
Section: Chemical Composition Of Banana Flourcontrasting
confidence: 74%
See 1 more Smart Citation
“…An important parameter of an ingredient used in bakery formulations is its lipid content. The BF analysed in this work had a lipid content of 2.69%, higher than the values reported by others for BF prepared from diverse unripe banana, being estimated to be between 0.33 and 0.82% [17]. The high lipid content reported here (in this work) could be due to that in our study a complete banana was used (peel and pulp).…”
Section: Chemical Composition Of Banana Flourcontrasting
confidence: 74%
“…In this sense, the nutritional/nutraceutical potential of unripe banana starch and fiber have been claimed by several authors [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the demonstration of protein phosphorylation as a mechanism for regulation of SPS activity, there is also experimental evidence that gene expression can make an important contribution to the overall increase in SPS activity in kiwifruits (LangenkaÈ mper et al 1998), citrus (Komatsu et al 1999) and bananas (Nascimento et al 1997). Previously (Nascimento et al 1997), we found that SPS transcription was increased during banana ripening, but that SPS transcripts and activity were at their highest several days before the onset of sucrose accumulation. At the same time the activation state, given by the ratio of activity under limiting/saturating conditions, did not change.…”
Section: Discussionmentioning
confidence: 51%
“…However, there is evidence that the amylolytic pathway should not be ruled out. The increase in several amylolytic enzymes, such as a-amylase, b-amylase, and a-glucosidases during ripening (Garcia and Lajolo 1988;Kitazato et al 1991), and also the large proportion of amylopectin in banana starch granules (Mota et al 2000) point to a coordinated action of both amylolytic and phosphorolytic starch degradation. Another piece of evidence to support this amylolytic pathway would be the presence of a-amylase, which is recognized as the only enzyme that can attack native starch granules (Hallett et al 1995;Sivak and Preiss 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation